2014
DOI: 10.1363/46e1314
|View full text |Cite
|
Sign up to set email alerts
|

Social Inequalities in Teenage Fertility Outcomes: Childbearing and Abortion Trends of Three Birth Cohorts In Finland

Abstract: This document is the author's final accepted version of the journal article. There may be differences between this version and the published version. You are advised to consult the publisher's version if you wish to cite from it. Social Inequalities in Teenage Fertility Outcomes: Childbearing and Abortion Trends of Three Birth Cohorts in FinlandHeini Väisänen and Michael Murphy London School of Economics and Political Science CONTEXT: Teenagers of low socioeconomic status are more likely to get pregnant, and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 43 publications
(144 reference statements)
0
11
0
Order By: Relevance
“…Weights were used to control for this design in the statistical analysis. The unweighted sample included almost half of the Finnish women in these cohorts; the amount of missing information was minimal (see Väisänen (2015) and Väisänen and Murphy (2014) for more information regarding the dataset).…”
Section: Data and Samplingmentioning
confidence: 99%
“…Weights were used to control for this design in the statistical analysis. The unweighted sample included almost half of the Finnish women in these cohorts; the amount of missing information was minimal (see Väisänen (2015) and Väisänen and Murphy (2014) for more information regarding the dataset).…”
Section: Data and Samplingmentioning
confidence: 99%
“…Abortions may be used to postpone, space, stop, or avoid childbearing (Bankole, Singh, and Haas 1998). The costs of childbearing for young women may be great if they have not yet completed their education, formed stable partnerships, or had time to accumulate economic resources (Becker 1991;Hansen et al 2009;Kreyenfeld 2010;Oppenheimer 1994;Väisänen and Murphy 2014). Some women are concerned that a new child will deprive existing children of parental and economic resources (Finer et al 2005;Kirkman et al 2009).…”
Section: Abortions and Previous Birthsmentioning
confidence: 99%
“…As information on cohabitation has only been included in the Finnish population registers since 1987, these women were young enough to have (almost) all of their cohabitations recorded and old enough in 2010, when data collection ended, to have experienced a sufficient number of abortions, births, and union dissolutions to enable the analyses. I extracted this data from a dataset collected for a larger study project (Väisänen 2015;Väisänen and Murphy 2014). The subsample I used in this study forms a simple random sample of 19,166 women born in these years.…”
Section: Datamentioning
confidence: 99%
“…A multi-site study in Vietnam interviewed women (n=1224) about repeat (≥ 2) abortions (Ngo et al, 2014). 1955-59, 1965-69, 1975-79) indicated that despite a decline in the overall teenage (≤ 19 years) pregnancy rate, teenagers who came from wealthier backgrounds had 2-3 times the odds of abortion (Väisänen and Murphy, 2014).…”
Section: Personal Characteristics That Shape Contextmentioning
confidence: 99%